Adaptable Particle-in-Cell algorithms for graphical processing units - Decyk, Viktor K.; Singh, Tajendra V. (Computer physics communications, 2011)
We developed new parameterized Particle-in-Cell algorithms and data structures for emerging multi-core and many-core architectures. Four parameters allow tuning of this PIC code to different hardware configurations. Particles are kept ordered at each time step. The first application of these algorithms is to NVIDIA graphical processing units, where speedups of about 15–25 compared to an Intel Nehalem processor were obtained for a simple 2D electrostatic code. Electromagnetic codes are expected to get higher speedups due to their greater computational intensity.